1994
DOI: 10.1073/pnas.91.19.8777
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of corticotropin-releasing factor receptor mRNA expression in the rat brain and pituitary.

Abstract: Corticotropin-releasing factor (CRF) is a major hypophysiotropic peptide regulating pituitary-adrenal response to stress, and it Is also widely expressed in the central nervous system. (2), with some major areas of mismatch (14). One potential basis for this discrepancy derives from the recent identification of a distinct CRF-binding protein (CRF-BP), which is prominently expressed in brain, including subsets of CRF-containing pathways and/or their targets (15). The identification of this distinct high-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
340
6
9

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(381 citation statements)
references
References 26 publications
26
340
6
9
Order By: Relevance
“…Little CRF 2 -mRNA signal was detected in the central nucleus of the amygdala. This nucleus plays a major role in the transduction of stress signals and contains a large cluster of CRF-expressing neurons, as well as modest amounts of CRF 1 -mRNA [2,10,14,31,38]. Current knowledge of the distribution of the two members of the CRF receptor family in the amygdala is insufficient to determine the relative roles of these receptors in mediating the effects of CRF on the hormonal and behavioral responses to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little CRF 2 -mRNA signal was detected in the central nucleus of the amygdala. This nucleus plays a major role in the transduction of stress signals and contains a large cluster of CRF-expressing neurons, as well as modest amounts of CRF 1 -mRNA [2,10,14,31,38]. Current knowledge of the distribution of the two members of the CRF receptor family in the amygdala is insufficient to determine the relative roles of these receptors in mediating the effects of CRF on the hormonal and behavioral responses to stress.…”
Section: Discussionmentioning
confidence: 99%
“…The CRF 2 receptor exists in at least two isoforms [22]. The distribution and expression of the two CRF receptors have been documented in the adult rat brain [10,31,47]. The differential anatomical distributions of the two receptors indicate that they may serve distinct functional roles.…”
Section: Introductionmentioning
confidence: 99%
“…Autoradiography and radioligand binding studies during early postnatal life in the rat have demonstrated changes in receptor number and regional distribution [5,6,11,12,15]. The two methods have yielded conflicting information regarding CRH receptor distribution in a number of brain regions [12,16,17]. A potential basis for this discrepancy derives from CRH binding protein which may interact with the CRH ligand [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…A potential basis for this discrepancy derives from CRH binding protein which may interact with the CRH ligand [12,16]. Binding studies may also provide limited information on the actual site of receptor synthesis because ligands may bind to neural receptors on cell bodies and along dendrites and axons [17]. The recent cloning of cDNAs encoding the rat CRH receptor [4,14] permits mapping the distribution of cells expressing CRH receptor messenger ribonucleic acid (mRNA) [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] There is a long body of evidence indicating disruption of hypothalamicpituitary-adrenal (HPA) axis function in depression, including the following key observations: increased 24-h elevations in cortisol production, 7 lack of suppression of plasma cortisol levels by dexamethasone, 8 increased concentrations of CRH in cerebrospinal fluid, 9 dysregulation of HPA responses to exogenous CRH administration [10][11][12] and loss of the negative correlation between plasma cortisol and continuously collected CSF CRH. 13 Of particular relevance, it has been demonstrated that antidepressants of various classes suppress CRH gene expression [14][15][16] in rodents and HPA activity in depressed 17 and healthy humans.…”
mentioning
confidence: 99%